The impact of individual comorbidities in transplant recipients receiving post-transplant cyclophosphamide - Spyridonidis, Alexandros; Labopin, Myriam; Savani, Bipin P; Kulagin, Alexander; Blaise, Didier; Broers, Annoek E C; Sica, Simona; Raiola, Anna Maria; Vydra, Jan; Choi, Goda; Rovira, Montserrat; Kwon, Mi; et al. (Bone marrow transplantation, 2025)
Post-transplant cyclophosphamide (PTCY) is increasingly used as effective graft-versus-host disease (GvHD) prophylaxis in allogeneic hematopoietic-cell transplantation (allo-HCT). However, PTCY is associated with toxicities. Whether patients with specific comorbidities are more vulnerable to cyclophosphamide-induced toxicity is unclear. We retrospectively evaluated the impact of individual organ dysfunctions for non-relapse mortality (NRM) risk and overall survival (OS) among 5888 adults who underwent PTCY-based allo-HCT for acute myeloid leukemia between 2010 and 2023. In multivariable analyses 5 of the comorbidities (renal, moderate/severe hepatic, cardiac including arrhythmia/valvular disease, severe pulmonary, infection) were independently associated with adverse NRM and OS without influencing relapse rate. A simplified model using the absence (n = 4390), presence of 1 (n = 1229) or presence of 2 or 3 (n = 269) of the comorbidities which were determined individually to contribute to NRM stratified patients into 3 NRM risk (16.2% vs. 21.6% vs. 36%, retrospectively) and OS categories (64% vs. 56% vs. 36.4%, retrospectively). In Cox model, recipients with 2 or 3 comorbidities had an increased hazard ratio for NRM of 2.38 (95% confidence interval [CI], 1.89-3) and for OS of 1.96 (95% CI 1.64-2.33). Whether patients with concomitant diagnoses, as determined here, may benefit from a reduced PTCY dose remains to be evaluated in prospective clinical trials.
Keywords: senioři; cyklofosfamid; Retrospective Studies; komorbidita; Middle Aged; mužské pohlaví; nemoc štěpu proti hostiteli; Leukemia, Myeloid, Acute; Adult; Hematopoietic Stem Cell Transplantation; ženské pohlaví; transplantace hematopoetických kmenových buněk; retrospektivní studie; Humans; Cyclophosphamide; Graft vs Host Disease; příjemce transplantátu; Transplant Recipients; Comorbidity; akutní myeloidní leukemie; lidé středního věku; dospělí; Female; Aged; lidé; Male